Drying of Banana Pseudo-stem Fibers: Evaluation of Kinetic Models, Effective Diffusivity, Thermodynamic Properties, and Structural Characterization - Genardo Queiroz de Oliveira; Rafael Alves do Nascimento; Juliana Ferreira Costa; Elza Brandão Santana; Cristiane Maria Leal Costa; Nielson Fernando da Paixão Ribeiro (Journal of Natural Fibers, 2022)
Banana pseudo-stem fiber drying was studied in a vertical fixed-bed convective dryer (60, 75, and 90°C). Nine mathematical models were used to analyze the drying behavior and the effective moisture diffusivity, activation energy, and thermodynamic properties were calculated. The dry fibers were evaluated by thermogravimetric, spectroscopic, and morphological analyses. High drying initial rates (25–30%) were observed indicating rapid evaporation of the free moisture present in the fibers. At the end of the process the moisture content decreased to 2.82, 0.14, and 0.16% (dry basis, db). The diffusion approximation model best fitted the experimental data and the effective diffusion coefficient increased with increasing temperature, reaching the order 10−7 m2 s−1. The activation energy required to initiate moisture removal from the fibers equaled 47.61 kJ mol−1, and contrary to the entropy and Gibbs free energy, the enthalpy decreased with increasing temperature, indicating that drying is an endergonic non-spontaneous process. Lignocellulosic absorption bands were identified and material degradation occurred at temperatures >190°C, according to thermogravimetric analysis. Morphological changes in the dry fibers mainly occurred at 90°C and led to structural damage. These changes were attributed to the tensile strength generated from the temperature and moisture gradients produced during drying.